Reuse of sheep wool fibers in the production of ultralightweight foamed concrete: effect of fiber treatment, length, and content on the mechanical properties (Fracture and Structural Integrity, 2024)
Concrete is one of the most widely used materials in the world. Still, its production processes, energy consumption, and high use of raw materials make it one of the most environmentally harmful materials. This study aims to enhance the sustainability of concrete by reducing the amount of binder and incorporating secondary materials into the cementitious matrix. The binder reduction is achieved by using a foaming agent that creates a microporous matrix, significantly decreasing the volume of cement in the material. Additionally, reinforcing the material with sheep wool fiber not only improves its mechanical properties but also gives a new purpose to a commonly discarded secondary material. The research specifically seeks to identify the most effective treatments for sheep wool fiber (including non-treated, salt-treated, lime-treated, NaOH-treated, and surfactant-treated fibers), as well as the optimal fiber length (6, 12, and 20 mm) and content (4.5, 9, and 15 kg/m³) for ultralightweight foamed concrete in terms of mechanical strength. The findings demonstrate excellent compatibility between wool fibers and ultralightweight foamed concrete, with fiber-reinforced samples showing up to a 60% increase in flexural strength and up to a 50% increase in compressive strength. Among the various fiber treatments evaluated, surfactant-treated fibers yielded the best results.
Keywords: Sheep wool fibers; Ultralightweight foamed concrete; Mechanical properties; Fiber reinforcement